2019
DOI: 10.1016/j.nicl.2019.101664
|View full text |Cite
|
Sign up to set email alerts
|

Increased brain age in adults with Prader-Willi syndrome

Abstract: Prader-Willi syndrome (PWS) is the most common genetic obesity syndrome, with associated learning difficulties, neuroendocrine deficits, and behavioural and psychiatric problems. As the life expectancy of individuals with PWS increases, there is concern that alterations in brain structure associated with the syndrome, as a direct result of absent expression of PWS genes, and its metabolic complications and hormonal deficits, might cause early onset of physiological and brain aging.In this study, a machine lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 83 publications
1
17
1
Order By: Relevance
“…For example, Cole and colleagues (Cole et al., 2015) explored the association between brain age delta and neuropsychological measures among traumatic brain injury subjects, and reported significant correlations between brain age delta values and memory as well as information processing speed. In another study, the correlation between brain age delta and body mass index as well as intelligence quotient was investigated among adults who suffer from Prader–Willi syndrome (Azor et al. 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Cole and colleagues (Cole et al., 2015) explored the association between brain age delta and neuropsychological measures among traumatic brain injury subjects, and reported significant correlations between brain age delta values and memory as well as information processing speed. In another study, the correlation between brain age delta and body mass index as well as intelligence quotient was investigated among adults who suffer from Prader–Willi syndrome (Azor et al. 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, this adult PWS population group represents a critical segment of the Registry in gaining an understanding of the natural history of PWS. Moreover, there are early reports of premature aging in the PWS population [28]. This is a poorly understood area and the Registry can help identify health issues in adults with PWS, as well as direct priorities for clinical care in adults with PWS.…”
Section: Discussionmentioning
confidence: 99%
“…Structural brain indices are hallmarks of individual differences in aging and health [ 161 ]. Gampawar et al reported a highly unique link between LTL and brain parenchymal fraction (BPF) in the elderly.…”
Section: Telomere and Brain Agingmentioning
confidence: 99%